Antiadherence and Antimicrobial Properties of Silver Nanoparticles against Streptococcus mutans on Brackets and Wires Used for Orthodontic Treatments - tovar, karla (2018)
White spot lesions (WSLs) are very frequent alterations during orthodontic treatments causing demineralization of the dental enamel. Various dental treatments have been developed to prevent WSLs; the prevalence and incidence of these lesions remain significantly high. Although silver nanoparticles (AgNPs) have demonstrated good inhibitory effects against several microorganisms, more studies about antiadherence activity on different orthodontic appliance surfaces are necessary. To determine the inhibitory effect and antiadherence activity of AgNPs on the adhesion of S. mutans on surfaces of brackets and wires for orthodontic therapies, two sizes of AgNPs were prepared and characterized. The evaluation of S. mutans adhesion was performed with microbiological assays on surfaces of brackets and orthodontic modules in triplicate. Topographic characteristics of orthodontic brackets and wires were made by scanning electron and atomic force microscopies. All AgNP samples inhibited S. mutans adhesion; however, the smaller AgNPs had better inhibition than the larger ones. The presence of the module influenced the adhesion of S. mutans but not in the activity of AgNPs. The AgNPs used in this study showed to have good antimicrobial and antiadherence properties against S. mutans bacteria determining its high potential use for the control of WSLs in orthodontic treatments.